2002
DOI: 10.1051/0004-6361:20011749
|View full text |Cite
|
Sign up to set email alerts
|

TeV candidate BL Lac objects

Abstract: Abstract. The TeV emission of low power BL Lac objects has been established by the detection of an handful of them. The knowledge of the level of the TeV emission and its spectrum can shed light on the particle acceleration mechanisms, and it is especially important to assess the still uncertain level of the far infrared background radiation, which can absorb the TeV photons through photon-photon interactions. In view of these implications, it is necessary to enlarge the number of TeV detected sources, and to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
289
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(309 citation statements)
references
References 75 publications
(70 reference statements)
18
289
2
Order By: Relevance
“…The discovery of this source as VHE γ-ray emitter demonstrates the importance of combining data at different wavelengths, namely radio, optical, X-ray, and the recently opened Fermi-LAT energy range, to help identify potential VHE γ-ray emitters. The MAGIC detection confirms the prediction made by Costamante & Ghisellini (2002) and Donato et al (2001) more than ten years ago, using X-ray, optical, and radio data. Of the 33 sources in the list they compiled, 21 have been already detected.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The discovery of this source as VHE γ-ray emitter demonstrates the importance of combining data at different wavelengths, namely radio, optical, X-ray, and the recently opened Fermi-LAT energy range, to help identify potential VHE γ-ray emitters. The MAGIC detection confirms the prediction made by Costamante & Ghisellini (2002) and Donato et al (2001) more than ten years ago, using X-ray, optical, and radio data. Of the 33 sources in the list they compiled, 21 have been already detected.…”
Section: Discussionsupporting
confidence: 87%
“…The BL Lac object 1ES 1727+502, which we discuss in this paper, is the latest in a long list of MAGIC discoveries of objects selected from X-ray catalogues (e.g. ), for 1ES 1727+502 Costamante & Ghisellini 2002, and for other sources, Donato et al 2001). Among those are 1ES 1218+30.4 (Albert et al 2006a), PG 1553+113 (Albert et al 2007a), 1ES 1741+196 ) and 1ES 0033+595 (Mariotti et al 2011).…”
Section: Introductionmentioning
confidence: 87%
“…This catalogue specifically selected HBLs and thus presented an obvious choice for the extension of the list of VHE BL Lac candidates. 1RXS J101015.9−311909 also fulfilled the criteria proposed in Costamante & Ghisellini (2002), where BL Lac candidates are considered interesting targets if they exhibit high levels of both X-ray and radio emission.…”
Section: Introductionmentioning
confidence: 94%
“…In Beckmann et al(2002) and Costamante & Ghisellini (2002), they also mention that the observed bolometric luminosity is thought to be well traced by the radio luminosity.…”
Section: Introductionmentioning
confidence: 98%